Rotary Parking System (RPS) - Alshaer, Mosab; Jondi, Mohammad; Samamra, Mohammad (Palestine Polytechnic University (PPU) - mechatronics, 2018)
Lack of space availability has always been a problem in urban areas and major cities and there are cars parked randomly on the streets that further limit the space. In order to handle the issue of parking in busy places various types of vehicle parking systems are used worldwide such as multi-level automated car parking. A rotary parking system (RPS) is a mechanical system that is designed to save the area that is required for parking cars. Like a multi-story parking garage, an RPS provides parking for cars on multiple levels stacked vertically to increase the number of parking spaces while saving land usage. However, the RPS utilizes a mechanical system to transport cars to and from parking spaces (rather than the driver) in order to eliminate much of the space wasted in a traditional parking. An RPS is more similar to an automated storage and retrieval system for cars. The present research is aimed to design and implementation a control system and model for the rotary automated car parking system to accommodate six cars.
CD, no of pages 55, 4/2018 ميكاترونيكس, in the store
Keywords: Rotary, Parking ,System (RPS)